Nitrogen dynamics in a Latosol cultivated with coffee - José A. Souza; Genelício C. Rocha; Mateus de P. Gomes; Carlos H. S. Rezende (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate nitrogen losses by NH3 volatilization and quantify the upward and downward NO3- flows in Latosol cultivated with arabica coffee. An experiment was set in 2010, in Viçosa-MG, Brazil (20º 41’ S and 42º 48’ W), in a randomized block design in a (3 x 2) + 1 factorial arrangement with three nitrogen doses (200, 400 and 600 kg ha-1), two forms of urea (conventional and NBPT urease inhibitor-treated) and one additional treatment without nitrogen fertilization, with four replicates. Semi-open type chambers were installed to quantify NH3 volatilization. To determine the concentration and flow of NO3- a soil solution extractor was installed in each plot at a 1-m depth together with three tensiometers at depths of 0.90, 1.00 and 1.10 m. Nitrogen losses by volatilization were 3.51 and 11.21% for NBPT-treated urea and conventional urea, respectively. The rainfall (1172 mm), its distribution and the dose strongly influenced the losses by leaching. Urease inhibitor-treated urea led to higher risk of groundwater contamination with NO3-. Returns of NO3- occur in periods of drought, but it is not possible to state if this NO3- can be used by the plant because, under these conditions, the soil has low moisture content, which may compromise the absorption.